Aviation Businesses During Covid-19: Airasia's Financial Challenges and Possible Way-outs - Nur Ainna Ramli; Nurshamimitul Ezza Ramli; Siti Fateha Zulkifli; Siti Nur Aqilah Ab Wahab (Fakultas Ekonomi dan Bisnis Islam, Institut Agama Islam Negeri Kerinci, 2024)
Non-Indexed Publication